The Role of Shaykh Al-Linggi in the Preservation of the Doctrine of Ahl al-Sunnah wa al-Jama'ah in the Malay World - Wan Zailan Kamaruddin bin Wan Ali (Jurnal Iman dan Spiritualitas, 2022)
The Malay world in the Southeast Asian region holds various Islamic -based scholarly and intellectual treasures, which have yet to be fully explored. Efforts to uncover valuable old treasures must be made continuously because of its various interests, especially in the framework of the development and advancement of the ummah. The region also saw the birth of influential Malay Muslim thinkers who drove the ummah towards excellence and glory. One of the figures discussed in this paper with the mission of "your service is remembered" is Muhammad Sa'id al-Linggi. Haji Muhammad Sa'id bin Haji Jamaluddin or better known as al-Shaykh Muhammad Sa'id al-Linggi al-Jawi (1875-1926) was one of the literary, religious figures from the Ahl al-Sunnah wa al-Jama'ah school of thought who famous in Negeri Sembilan in the late 13th/19th century and early 14th/20th century and is considered to have a significant influence on society, especially in Negeri Sembilan, Malaysia and even the Southeast Asian region.